2016
DOI: 10.1371/journal.pone.0160141
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Alloy Implant Debris Induces Inflammation and Bone Loss Primarily through Danger Signaling, Not TLR4 Activation: Implications for DAMP-ening Implant Related Inflammation

Abstract: Cobalt alloy debris has been implicated as causative in the early failure of some designs of current total joint implants. The ability of implant debris to cause excessive inflammation via danger signaling (NLRP3 inflammasome) vs. pathogen associated pattern recognition receptors (e.g. Toll-like receptors; TLRs) remains controversial. Recently, specific non-conserved histidines on human TLR4 have been shown activated by cobalt and nickel ions in solution. However, whether this TLR activation is directly or ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 56 publications
2
46
0
Order By: Relevance
“…The NLRP3 inflammasome, however, appears to supersede TLR4 signaling in prosthetic-wear particle-induced osteolysis (147). On the other hand, the non-NLR inflammasome AIM2 and not NLRP3 may mediate the acute phase of PMMA-induced foreign body responses (148).…”
Section: Figure 2 the Inflammasomes In Osteolysismentioning
confidence: 99%
“…The NLRP3 inflammasome, however, appears to supersede TLR4 signaling in prosthetic-wear particle-induced osteolysis (147). On the other hand, the non-NLR inflammasome AIM2 and not NLRP3 may mediate the acute phase of PMMA-induced foreign body responses (148).…”
Section: Figure 2 the Inflammasomes In Osteolysismentioning
confidence: 99%
“…It may be misleading that several past investigations have shown that smaller particles (e.g., 0.4 μm) produce a greater inflammatory response than larger particles (e.g., 7.5μm), because in these past studies equal mass of debris was used which generally resulted in >1,000‐fold higher dose of smaller particles per cell than larger particles per cell. Thus, the >0.8 μm sized stainless steel particles used in this investigation, while not nanometer in size (<300 nm), fall into the smaller sub‐micron ranges of particles that have been reported as optimally reactive and are in the range of TJA implant particulate debris.…”
Section: Discussionmentioning
confidence: 81%
“…Aseptic loosening of orthopedic implants is described as a immunological response against wear particles eroded from the implant and was first reported by Harris et al21 It is well established in orthopedic research that wear debris and nanoparticles from different metals can cause osteolysis by activation and secretion of the pro‐inflammatory cytokines (for example, interleukin (IL)‐1β, IL‐6, tumor necrosis factor (TNF)‐α, and prostaglandin E2 (PGE2) 22, 23, 24, 25, 26, 27, 28…”
Section: Introductionmentioning
confidence: 99%
“…Aseptic loosening of orthopedic implants is described as a immunological response against wear particles eroded from the implant and was first reported by Harris et al 21 It is well established in orthopedic research that wear debris and nanoparticles from different metals can cause osteolysis by activation and secretion of the pro-inflammatory cytokines (for example, interleukin (IL)-1b, IL-6, tumor necrosis factor (TNF)-a, and prostaglandin E2 (PGE2). [22][23][24][25][26][27][28] In dentistry, very little has been discussed about this particle-induced inflammatory process that could occur around a dental implant. As in osteolysis around an orthopedic implant, 29 peri-implantitis shows a similar infiltration of macrophages, and the macrophage infiltration is more pronounced in peri-implantitis than in an infectious disease such as periodontitis.…”
Section: Introductionmentioning
confidence: 99%